2016
DOI: 10.3168/jds.2015-10140
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on fine milk composition for breeding and management of dairy cows

Abstract: The challenge of managing and breeding dairy cows is permanently adapting to changing production circumstances under socio-economic constraints. If managing and breeding address different timeframes of action, both need relevant phenotypes that allow for precise monitoring of the status of the cows, and their health, behavior, and well-being as well as their environmental impact and the quality of their products (i.e., milk and subsequently dairy products). Milk composition has been identified as an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 51 publications
0
65
0
Order By: Relevance
“…The DP method has some benefits over the IP method: there is no need to predict phenotypes from the spectra to estimate the EBV for the traits, and EBV are predicted once (only for the spectra) and then used to derive the EBV of traits. This is particularly relevant when considering the high number of traits for which FTIR calibration equation are being developed (Bonfatti et al, 2016;Gengler et al, 2016). In addition, direct analysis of the spectral variables may increase the precision of the estimated genetic parameters and the accuracy of EBV predictions and genetic gains, particularly for low-heritability traits, as a consequence of exploiting the genetic relationships among many spectral variables (Dagnachew et al, 2013b).…”
Section: Comparison Between Direct and Indirect Methods For Exploitingmentioning
confidence: 99%
“…The DP method has some benefits over the IP method: there is no need to predict phenotypes from the spectra to estimate the EBV for the traits, and EBV are predicted once (only for the spectra) and then used to derive the EBV of traits. This is particularly relevant when considering the high number of traits for which FTIR calibration equation are being developed (Bonfatti et al, 2016;Gengler et al, 2016). In addition, direct analysis of the spectral variables may increase the precision of the estimated genetic parameters and the accuracy of EBV predictions and genetic gains, particularly for low-heritability traits, as a consequence of exploiting the genetic relationships among many spectral variables (Dagnachew et al, 2013b).…”
Section: Comparison Between Direct and Indirect Methods For Exploitingmentioning
confidence: 99%
“…A study of SNP associated with subclinical ketosis in US Jerseys (Fugate et al, 2014) reported that genotypes could be useful for predicting predisposition for ketosis. Another promising avenue is the use of mid-infrared (MIR) data to predict ketosis because of its association with energy balance (Gengler et al, 2015). In the United States, data from on-farm herd management systems may be sufficient for routine calculation of genetic and genomic evaluations for most common health disorders of US Holsteins (Clay et al, 2013;Cole et al, 2013).…”
Section: Other Health Traitsmentioning
confidence: 99%
“…Mid-infrared (MIR) spectroscopy is routinely used by worldwide milk recording organizations to quantify the concentration of fat, protein, and lactose in milk samples. Moreover, an increasing number of studies have reported a good capability of MIR to predict traits related to cow metabolic status, such as energy balance, milk and serum fatty acids, and BHB [see reviews by De Marchi et al (2014) and Gengler et al (2016)], which are known to affect fertility (Ribeiro et al, 2013). Also, Toledo-Alvarado et al (2018b) reported that milk fatty acid profiles predicted by MIR could be used to identify cows in proestrus or estrus.…”
Section: Introductionmentioning
confidence: 99%